ANÁLISIS COMPARATIVO DE LA ALIMENTACIÓN DEL GATO MONTÉS (LYNX RUFUS) EN DOS DIFERENTES AMBIENTES DE MÉXICO - Aranda, Marcelo; Rosas, Octavio; Ríos, José De Jesús; García, Nashieli (Instituto de Ecología, A.C., 2002)
Feeding habits of the bobcat (Lynx rufus) in two different localities of Mexico were studied by the analysis of 197 and 922 scats. Lagomorphs, and rodents were the more important prey items in both places. At El Plomito, state of Sonora, we found 18 different prey species, and the most important were Sylvilagus audubonii (35.5%), Lepus sp. (31.5%), Neotoma albigula (14.0%), Odocoileus sp. (2.9%), and Spermophilus variegatus (1.7%), while in El Ajusco, central Mexico, we found 28 prey species, and the most important were Sylvilagus floridanus (41.6%), Sylvilagus cunicularius ((15.4%), Romerolagus diazi (12.3%), Cratogeomys merriami (5.1%), and Sciurus aureogaster (4.9%). Our results support the theory that the bobcat, like other lynxes, is specialized to prey on rabbits and hares. s.